Management of Organizing Sports Classes at Public Junior High School 1 Bodeh Pemalang Regency - Triyatmo, Endro; Soegiyanto, Soegiyanto; Ciptaning Wahyu W., Imam Santosa (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this study was to describe and analyze the management of the implementation of sports classes at Public Junior High School 1 Bodeh in Pemalang district which focused on the main problems, namely: (1) organizing, (2) students, (3) workforce, (4) curriculum and training programs, (5) infrastructure, and (6) funding. In this study, a qualitative approach was used. Data collection techniques use interview, observation and documentation techniques. The data sources were taken from the Sports Class Implementation Team. Data validity is obtained by triangulation. Data were analyzed by (1) data reduction, (2) data presentation, and (3) concluding. The results of the study showed that the management of sporting classes at Public Junior High School 1 Bodeh in Pemalang district was generally good by the Guidelines for the implementation of sports class programs. Sports class coaching organization at Public Junior High School 1 Bodeh has established good relations with the local government but has not established cooperation with universities in order to implement sports science and technology. Management of students has run well, starting from recruitment, implementation of learning, and implementation of training programs. Manpower management is also good enough, physical education teachers in sports classes are qualified, while the trainer has a minimum training certificate. For the sports class curriculum, it has been running well with the regular class curriculum, namely the 2013 curriculum with its syllabus for physical education subjects plus more material on the branches of Athletics, Volleyball, and Artistic Gymnastics in accordance with the sports developed at Public Junior High School 1 Bodeh, As for the sports class training program at Public Junior High School 1 Bodeh has not gone well, the management of sports class infrastructure facilities at Public Junior High School 1 Bodeh has run well. The management of funding for the sports class program at Public Junior High School 1 Bodeh has run quite well, ranging from the use of its aid funds and reporting.